Osteoporosis in postmenopausal women - Marques, Laura (2003)
The osteoporosis in postmenopausal women is, in most cases of type I. Loss of bone mass is due to a deficiency of oestrogens. In the approach of osteoporosis in these women, it is important to consider the risk factors. To this end, a careful history and well prepared may lift the diagnosis of osteoporosis, since the clinic is usually poor or nonexistent until the first fracture appears. The secondary cause of osteoporosis should always be investigated, since all diagnostic and therapeutic approach will depend on the underlying cause. The diagnosis of osteoporosis is made primarily by the determination of bone mineral density, following the standards of the World Health Organization The treatment of osteoporosis in postmenopausal women, has the cornerstone prevent the appearance of cracks and passes through a non-pharmacological approach and, where necessary, pharmacology. The pharmacological treatment is particularly indicated for women with risk factors of fracture, or those who have already suffered breakage. In conclusion we present some proposed clinical approach to prevention and treatment of osteoporosis in women post - menopausal.